Sedimentologia do talude continental frente ao Município de Luís Correia, Piauí - Lopes, Jeziel Pena Forte (2018)
Due to the location of the continental slope within the continental margin and its difficulty of access, there are few studies that characterize its sediments. In this way, the present work focuses on the continental slope in order to define its sedimentology. The study was carried out from two testimonies (SIS 699 and ANP 1285) located on the continental slope of the state of Piauí, in front of the coast of the municipality of Luís Correia, approximately 86 km from the coast. Geologically it is located in the Piauí-Camocim subbasin, belonging to the Ceará basin, which is located on the Brazilian equatorial margin, covering an area of approximately 34,000 km2. Through the bibliographical research, field activity and laboratory analysis, the sedimentological study of the area was carried out. From the analysis of the testimonies, it is possible to characterize the upper and lower continental slope of Luís Correia, Piauí. The SIS 699 testimony is predominantly composed of silt, marking a low energy environment with suspension transport. This sediment is silicibioclastic, classified as sandy mud. It is marked by relatively low carbonate contents and high C / N ratio, evidencing the dominance of terrigenous particles in this region. The influence of these particles is evidenced by the frequency of grains of quartz, kaolinite and haloisite, as well as the appearance of highly altered grains. The dominant paleoclimate is the tropical humid, marked by the appearance of kaolinite. The contribution of pelagic particles is marked by biogenic sediments such as planktonic and benthic foraminifera transported by suspension. The ANP 1285 is composed of bioclastic and biosiliciclastic sediments, classified as limestone and calcareous loam, respectively. It is marked by low energy sedimentation, with great contribution of pelagic particles as foraminifera and a lower influence of terrigenous grains evidenced by the presence of quartz, kaolinite, montmorillonite, potassic feldspar and ilite. It was possible to observe the transition from arid paleoclimate, marked by montmorillonite, to a humid tropical climate, indicated by kaolinite. Based on the analyzes, it is possible to characterize the testimonies as upper continental slope and lower continental slope of Luís Correia, Piauí. The upper continental slope of Piauí was characterized from SIS 699, being in lower depth and shorter distance from the coastline, marked by the greater contribution of terrigenous sediments in its sedimentation. The lower continental slope of Piauí, described on the basis of ANP 1285, is in greater depth, as well as a greater distance from the coastline, marked by the dominance of pelagic particles in the sedimentation.